2021
DOI: 10.1136/bmjopen-2021-050317
|View full text |Cite
|
Sign up to set email alerts
|

Association between egg consumption and metabolic syndrome in Chinese population: a cross-sectional study

Abstract: ObjectivesMetabolic syndrome (MS) comprises a constellation of symptoms that include abdominal obesity, hypertension, hyperglycaemia and dyslipidaemia. Dietary intake is a crucial environmental risk factor for MS, but the exact association between MS and egg consumption, which accounts for more than half of the daily total cholesterol intake in Chinese population, has not been previously studied. The aim of this study was to examine the correlation between dietary egg consumption and the prevalence of MS in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A cross-sectional study on 1,008 Irish middle-age men and 1,039 women showed diet as an important determinant of the obesity phenotype and general health condition 31 . In a cross-sectional study on adults, Wang et al declared that egg consumption was inversely related to metabolic syndrome, particularly in female individuals 32 . In contrast, the HELENA study on Spanish adolescents revealed that egg consumption was not related to blood pressure, insulin resistance, adiposity, lipid profile, and cardio-respiratory fitness 33 .…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study on 1,008 Irish middle-age men and 1,039 women showed diet as an important determinant of the obesity phenotype and general health condition 31 . In a cross-sectional study on adults, Wang et al declared that egg consumption was inversely related to metabolic syndrome, particularly in female individuals 32 . In contrast, the HELENA study on Spanish adolescents revealed that egg consumption was not related to blood pressure, insulin resistance, adiposity, lipid profile, and cardio-respiratory fitness 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In the two cohorts of 5,251 Koreans and 5,324 Australians, compared with the lowest quartile group, no significant association was found between egg intake and MetS in the highest quartile group ( 12 , 13 ). In a cross-sectional study of 11,529 people in China, it was found that the risk of MetS in people who consumed >7 eggs per week was 18% lower than that those who consumed < 3 eggs (OR = 0.82, 95% CI = 0.74–0.91) ( 10 ). In another cross-sectional study of 8,241 people in China, it was found that the risk of MetS of consuming >1 egg per day was 1.18 times that of consuming < 1/2 egg per day (40–50 g per egg) ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 8 , 9 ). Eggs were found to be negatively associated with MetS in a prospective study in Korea and a cross-sectional study in China ( 7 , 10 ), while a positive association was found in an Iranian cohort ( 11 ), and no significant association was found in an Australian and another Korean cohort ( 12 , 13 ). At present, there are limited studies on eggs and CMFs at home and abroad, and most of them are cross-sectional studies.…”
Section: Introductionmentioning
confidence: 93%
“…Some of the egg nutrients are essential during pregnancy, infancy, and early childhood due to the content of iodine, choline, and DHA unsaturated acids [ 100 ]. Higher egg consumption may also lower the risk of multiple sclerosis [ 21 ]. Research conducted in China by Xia et al [ 101 ] indicated that both low and high egg consumption may lead to cardiovascular disease, therefore, it is suggested to consume less than 6 eggs per week.…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers consider the aspect of sustainable consumption of food products through narrow sections of it. Sustainable consumption of animal products is most often analyzed into subgroups, including: meat [ 8 , 11 , 12 , 13 ], fishes [ 14 , 15 , 16 , 17 ], and eggs [ 18 , 19 , 20 , 21 ], in which frequently declared consumer attitudes are analyzed [ 22 ]. Based on the above, our research has tried to associate consumption reports with specific questions about lifestyle and choice preferences to contribute to global sustainability through the European context.…”
Section: Introductionmentioning
confidence: 99%